A conceptual study of digital transformation, human resource competence, and adaptive leadership on Employee performance in public sector organizations - Ferdinandus Christian; Asadur Rahman Muhammad; Dyah Widowati; Siti Mahmudah; Moch Aminudin Hadi (Indonesian Indovisi Institute, 2026)
This conceptual study addresses the persistent gap between digital transformation initiatives and employee performance improvement in public sector organizations. It aims to develop an integrated explanatory understanding of how digital transformation shapes employee performance through human resource competence and adaptive leadership. The study uses a literature-based methodology, relying on written scholarly sources (books, journal articles, prior research, and academic reports) as the primary and secondary data base. The analysis employs content analysis to identify conceptual patterns and relationships among the three constructs and their connection to employee performance mechanisms. The findings indicate that digital transformation becomes performance-effective when employees possess the relevant human resource competence to operate within redesigned workflows and when adaptive leadership organizes learning, clarifies priorities, and coordinates implementation under uncertainty. The study concludes that performance outcomes are best explained through a mechanism-based linkage rather than a technology-only perspective in public sector contexts.